The Nature of Technological Change: Its Implications for Work and Labour Regulation - Smith, Anthony E. (Relations industrielles / Industrial Relations, 1992)
Recent developments in the new technology debate suggest that the effects of technological change may be more complex and ambiguous than managerialist and labor process writers have argued. The process of technological change in an employing organization involves a number of distinct stages. A recent study challenged the position that technological change brings about the deskilling of workers. It is demonstrated that the independent influence of technology is a necessary compliment to an examination of the way outcomes of change are chosen and negotiated. The study used a set of survey data based on 435 unionized employing organizations in Atlantic Canada.
Keywords: Automation; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Hypotheses; Implications; Labor; Labor Unions; Labor force; Microelectronics; Polls & surveys; Production planning; Regression analysis; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Technological change; Theory